Spillover Effects of Financial Development on Renewable Energy Deployment and Carbon Neutrality: Does GCC Institutional Quality Play a Moderating Role? - Hamed, Wesam M. A. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
When viewed through the lens of sustainable ecology, the importance of financial sustainability increases. Consequently, this thesis investigates the influence of financial development on carbon emissions and renewable energy in Gulf Cooperation Council (GCC) nations during the period from 2005 to 2020. In addition to controlling for economic growth, technological innovation (mobile subscription), trade openness, and service value added, this study modifies the relationship by considering institutional quality (including regulation quality, rule of law, control of corruption, voice and accountability, and political stability). In contrast, the quantile-on-quantile regression method was employed for the investigation, whereas the fixed effect ordinary least squares (OLS) and Driscoll Kraay OLS methods were utilized as robustness checks. From model 1 where renewable energy is the dependent variable, it was observed that, there was a positively significant relationship between financial development, urbanization, economic growth, trade openness, service value added as well as institutional quality indicators (governance indicators) with the dependent variable (renewable energy development) while technology innovation (mobile subscription) had a negative connection with the dependent variable (renewable energy). Nevertheless, it was observed from the Model 2 where carbon emission is the dependent variable, there was a positive connection between financial development, technology innovation (Mobile subscription), and service value added with carbon emission. Moreover, Urbanization, economic growth, trade openness and institutional iv quality indicators (governance indicators) had a negative connection with the dependent variable (carbon emission). This result suggests that additional investments in renewable energy enterprises serve as an intermediary for the liquidity of banks in the countries under investigation. Additionally, this research contributes to the existing body of knowledge by conducting a comparative analysis of the financial development, specifically the capital adequacy of banks, in GCC countries that are frontrunners in climate finance. It emphasizes the significance of bank capital adequacy in bolstering environmental legislation and encouraging investments in renewable energy.

ÖZ: Sürdürülebilir ekoloji merceğinden bakıldığında finansal sürdürülebilirliğin önemi artıyor. Sonuç olarak, bu tez, Körfez İşbirliği Konseyi (KİK) ülkelerinde 2005'ten 2020'ye kadar olan dönemde finansal kalkınmanın karbon emisyonları ve yenilenebilir enerji üzerindeki etkisini araştırıyor. Ekonomik büyümeyi, teknolojik yeniliği (mobil abonelik), ticari açıklığı ve hizmet katma değerini kontrol etmenin yanı sıra bu çalışma, kurumsal kaliteyi (düzenleme kalitesi, hukukun üstünlüğü, yolsuzluğun kontrolü, söz hakkı ve hesap verebilirlik dahil olmak üzere) ve kurumsal kaliteyi dikkate alarak ilişkiyi değiştirmektedir. politik istikrar). Buna karşılık, araştırma için kantil üzerinde kantil regresyon yöntemi kullanılırken, sağlamlık kontrolleri olarak sabit etkili sıradan en küçük kareler (OLS) ve Driscoll Kraay OLS yöntemleri kullanıldı. Yenilenebilir enerjinin bağımlı değişken olduğu Model 1'den, finansal gelişme, kentleşme, ekonomik büyüme, ticari açıklık, hizmet katma değeri ve kurumsal kalite göstergeleri (yönetişim göstergeleri) ile bağımlı değişken arasında pozitif yönde anlamlı bir ilişki olduğu görülmüştür. değişken (yenilenebilir enerji gelişimi) ile teknoloji yeniliği (mobil abonelik) bağımlı değişken (yenilenebilir enerji) ile negatif bir bağlantıya sahiptir. Bununla birlikte, karbon emisyonunun bağımlı değişken olduğu Model 2'de finansal gelişme, teknoloji yeniliği (Mobil abonelik) ve karbon emisyonu ile hizmet katma değeri arasında pozitif bir bağlantı olduğu görülmüştür. Ayrıca kentleşme, ekonomik büyüme, ticari açıklık ve kurumsal kalite göstergeleri (yönetişim göstergeleri) bağımlı değişken (karbon emisyonu) ile negatif bir bağlantıya sahiptir. Bu sonuç, yenilenebilir enerji işletmelerine yapılan ek yatırımların, incelenen ülkelerde bankaların likiditesine aracılık ettiğini göstermektedir. Ek olarak bu araştırma, iklim finansmanında öncü olan Körfez İşbirliği Konseyi ülkelerindeki finansal gelişmenin, özellikle de bankaların sermaye yeterliliğinin karşılaştırmalı bir analizini yaparak mevcut bilgi birikimine katkıda bulunuyor. Çevre mevzuatının güçlendirilmesi ve yenilenebilir enerji yatırımlarının teşvik edilmesinde banka sermaye yeterliliğinin önemini vurgulamaktadır.
Doctor of Philosophy in Finance. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2024. Supervisor: Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance Department; Stock Markets--Stock Exchanges; Capital movements--Volatility Spillovers; Financial development, Bank adequacy, Renewable energy, Carbon emission, Institution quality, GCC countries.